2017
DOI: 10.1097/hco.0000000000000385
|View full text |Cite
|
Sign up to set email alerts
|

Molecular basis of familial hypercholesterolemia

Abstract: The phenotype of familial hypercholesterolemia is caused by more than 1700 mutations the LDLR, apoB and PCSK9 genes, which explains approximately 85% of familial hypercholesterolemia cases. By means of next-generation sequencing, an increasing number of mutations in established and putative novel genes associated with this phenotype have been identified.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 46 publications
0
15
0
Order By: Relevance
“…Binding between the LDL receptor and apoB100 only occurs after the polypeptide has undergone a conformational change which results due to the lipolysis of VLDL to LDL [ 59 , 60 ]. Loss-of-function mutations in the LDL receptor or apoB can result in familial hypercholesterolemia, which is characterized by extremely elevated plasma LDL levels, thus leading to accelerated atherosclerosis [ 61 ]. Additionally, gain-of-function mutations in PCSK9, a proprotein convertase that accelerates the degradation of the LDL receptor, also results in high LDL concentrations [ 62 ].…”
Section: Apob: Characteristics and Compositionmentioning
confidence: 99%
“…Binding between the LDL receptor and apoB100 only occurs after the polypeptide has undergone a conformational change which results due to the lipolysis of VLDL to LDL [ 59 , 60 ]. Loss-of-function mutations in the LDL receptor or apoB can result in familial hypercholesterolemia, which is characterized by extremely elevated plasma LDL levels, thus leading to accelerated atherosclerosis [ 61 ]. Additionally, gain-of-function mutations in PCSK9, a proprotein convertase that accelerates the degradation of the LDL receptor, also results in high LDL concentrations [ 62 ].…”
Section: Apob: Characteristics and Compositionmentioning
confidence: 99%
“…Of these death numbers, roughly 7.4 million were due to coronary heart disease and 6.7 million were due to stroke (WHO, 2016 ). Hypercholesterolemia, one of the major risk factors for atherosclerosis and developing CVD, is characterized by high level of low density lipoprotein (LDL) cholesterol (LDL-C) in plasma (Newman et al, 1986 ; Lusis, 2000 ; Hopkins et al, 2011 ; Varghese, 2014 ; Bruikman et al, 2017 ). LDL particles are removed from the circulation mainly by hepatic uptake via the LDL receptor (LDLR).…”
Section: Introductionmentioning
confidence: 99%
“…FH heterozygotes account for 1/20 of those presenting with early CAD and ~ 5% of myocardial infarctions (MIs) in persons below 60 years of age . It has been suggested that the prevalence of FH is 1 in 230–250 individuals and that < 1% of FH patients have been identified across the globe . FH heterozygote plasma cholesterol levels are twice as high as normal, resulting in distinctive cholesterol deposits (xanthomas) in tendons and skin.…”
mentioning
confidence: 99%